Generative AI Adoption in Indonesian Secondary Education: A Case Study of SMP Negeri 1 Dawuan Majalengka Regency - Ahmad Andi Rizaldi; Tio Fanky Kresnandya (Journal on Smart Learning Technologies, 2025)
The rapid proliferation of Generative Artificial Intelligence (GenAI) tools, such as ChatGPT, Deepseek, and Gemini, has introduced new paradigms in global education. While the impact of these tools on higher education is increasingly documented, there is a paucity of research regarding their penetration and usage patterns at the junior high school level (Sekolah Menengah Pertama) in Indonesia. This study aims to fill this gap by investigating the frequency, nature, and academic implications of GenAI usage among students at SMP Negeri 1 Dawuan. Utilizing a quantitative descriptive survey, the study assesses how frequently students engage with these technologies and for what specific academic purposes, such as writing assistance, problem-solving, or information retrieval. The findings reveal that while students are highly aware of these tools, they primarily use them for instant answer retrieval rather than deep learning. Furthermore, the study identifies a tension between the benefits of enhanced learning efficiency and the risks of cognitive over-reliance. These results suggest that while GenAI holds significant potential for supporting digital natives, there is an urgent need for a firm policy and fixed regulation regarding AI usage in the school to ensure these tools are used ethically and constructively in the Indonesian secondary school context.